Early Detection of Postpartum Depressive Symptoms in Mothers and Fathers and Its Relation to Midwives’ Evaluation and Service Provision: A Community-Based Study - Anding, Jana; Röhrle, Bernd; Grieshop, Melita; Schücking, Beate; Christiansen, Hanna (Frontiers in Pediatrics, 2015)
Background: Postpartum parental mental health problems pose a serious risk for child development and often remain undetected in postpartum primary care. Within the framework of the German Midwifes Prevention Study, the aim of this study was to investigate the presence of postpartum emotional distress in mothers and fathers, and the detection of distressed parents by midwives in a primary care setting. We also examined whether a temporal extension of the postpartum midwife care period is associated with greater use of midwife contacts and higher rates of referral to further professional support if needed. Methods: Mothers, fathers, and midwives filled out questionnaires at two weeks (t1) and six months (t2) postpartum. Compared to standard care in the control group (CG), midwives in an intervention group (IG) offered extended postpartum care of six months postpartum. Parental psychological distress was assessed using the Edinburgh Postnatal Depression Scale (EPDS). Midwives reported on parental psychological distress as well as the number of postpartum contacts and referrals to additional social care and health providers. Results: Based on their ratings, midwives identified half of mothers and around one quarter of fathers with elevated depressive symptoms according to the EPDS at t1 and t2. IG mothers used significantly more midwife contacts than CG mothers. IG mothers with high postnatal psychological distress at t2 used significantly more contacts than mothers with lower levels of distress. IG mothers with high psychological distress at t2 were referred to additional support services more often than mothers with lower levels of distress.